(untitled) (Bangladesh Medical Journal, 2014)
Pulmonary tuberculosis may be easily confused with other chest diseases during its initial presentation. This study was carried out to identify presenting clinical and laboratory features that differentiate pulmonary tuberculosis from other diseases and to correlate clinical features and radiological findings. This study was conducted in department of pediatrics and Radiology in Bangabandhu Sheikh Mujib Medical University and Dhaka Shihsu Hospital from July 2005 to June 2006. A total fifty Children below 18 were included in the study after being clinically diagnosed as pulmonary tuberculosis. These patients were subjected to detailed history and, clinical examination. Each patient was evaluated by blood CBC, ESR, Mantoux test, Chest X-ray posterior anterior/lateral view, BCG test and gastric lavage. Statistical analysis was performed by SPSS 8 computer program. Fever, cough, weight loss, night sweats and raised ESR were the most common findings in PTB children. No correlation was found between clinical and laboratory parameters in establishing a confident diagnosis of the disease. The study highlights the importance of further research to pinpoint stronger and more reliable criteria for diagnosis. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18974 Bangladesh Med J. 2013 Jan; 42 (1): 21-24